Material handling management in the iron ore supply chain process to meet grade and tonnage requirements - Parra Trouchina, Oscar Javier (Curtin University, 2024)
The research focuses on optimizing mining operations to meet ore tonnage targets while controlling grade variability. It highlights the challenges of handling diverse materials and reactive processes that lead to lower-quality products or penalties. By exploring alternative strategies, such as strategic rehandling and blending low-grade materials, the study aims to improve grade consistency and profitability. A new mathematical model is proposed to create tactical plans that maximize profit, metal content, and material movement, with a comparison of results based on grades, tonnages, and contaminants.